Genetic characterization of bovine herpesvirus 4 (BoHV-4) isolates from Argentine cattle suggests a complex evolutionary scenario - Perez, Sandra (2020)
Bovine herpevsirus 4 (BoHV-4) is a gammaherpesvirus that has been associated with different clinical conditions in cattle. In Argentina, BoHV-4 was detected in diverse bovine samples. The aim of this study was to analyze the genetic relationship of 48 field BoHV-4 strains isolated from cattle in Argentina. According to thymidine kinase (tk) gene sequences, BoHV-4 isolates belong to genotypes 1, 2 and 3. Phylogenetic analyses confirmed the presence of the three previously described viral genotypes. However, some of the studied isolates presented conflicting phylogenetic signals between the studied markers. This suggests a complex evolutionary background, that is a history of recombination, incomplete lineage sorting (deep coalescence) or a combination of these, which requires further study. These potential events make difficult the diagnosis of BoHV-4 from clinical samples of cattle and may pose a significant problem for the control of the virus in the herds.